ANALYSIS OF FACTORS FOR SELECTION OF CONVENTIONAL PUBLIC TRANSPORTATION MODES AND ONLINE PUBLIC TRANSPORTATION IN MAGETAN DISTRICT - Purnomo, Habil Inanda; Moetriono, Hary (Jurnal Teknik Sipil, 2023)
One important aspect of transportation is the choice of mode. Mode selection, as one of the steps in transportation planning. Mode selection plays an important role in determining transportation policy issues, in relation to the types of modes and infrastructure available. This study aims to analyze the choice of modes of online public transportation and conventional public transportation for people in Magetan Regency. Using multiple linear regression analysis, this study also tries to measure the factors that influence the choice of online public transportation modes and conventional public transportation in Magetan Regency. In addition, this study aims to measure the probability of choosing online public transportation modes and conventional public transportation for people in Magetan Regency using stated preference and binomial logit analysis. Based on data from 300 respondents, the results showed that 243 people chose online public transportation and 57 people chose conventional public transportation. The results of multiple linear regression analysis show that all variables in this study are accepted. The results of the probability measurement show that the probability of people choosing online public transportation is worth 0.696 and the probability of people choosing conventional public transportation is worth 0.304.